Growing Up in a Foreign Land: A Narrative Analysis from a Childist Perspective of Hananiah, Mishael, and Azariah in Daniel 1–2 - Pasterkamp, Laura (Biblical interpretation, 2025)
This paper analyses the role and position of Hananiah, Mishael, and Azariah in the narratives of the first two chapters of Daniel from a childist perspective and with an intersectional lens, in order to explore how their identity as children instead of the ‘young men’ they have often been taken for, changes our interpretation of the narratives. A narrative analysis of the texts shows that the three characters, in a vulnerable and formative phase of their lives as growing boys in a foreign land, act extraordinarily bravely for their age by rejecting the king’s diet and grow into mature men who are able to take on the responsibility of governing a province.